Early epilepsy surgery for non drug-resistant patients - Veronica Pelliccia; Francesco Deleo; Francesca Gozzo; Ginevra Giovannelli; Roberto Mai; Massimo Cossu; Laura Tassi (Epilepsy & Behavior Reports, 2022)
The aim of epilepsy treatment is to achieve seizure freedom. Surgery is often still considered a late option when pharmacological treatments have failed and epilepsy has become drug-resistant.We analyse the clinical features and surgical outcome in patients who underwent surgery without experiencing drug-resistance comparing with those observed in patients who became drug-resistant.Two-hundred and fifty patients with symptomatic focal epilepsy (12.1% of patients who underwent surgery at the “Claudio Munari” Epilepsy Surgery Center) were selected on the basis of initial period of seizure freedom and followed-up for at least 12 months. Patients were divided into two groups: those who underwent surgery during the initial period of seizure freedom (n = 74), and those who underwent surgery after an initial seizure-free period followed by drug-resistance (n = 176).Outcomes were significantly better in non-drug-resistant patients (p < 0.001), all of whom had Engel class Ia or Ic. In the drug-resistant group, 136 patients (77.3%) had class Ia or Ic. The median post-operative follow-up was respectively 75.0 and 84.0 months.Epilepsy surgery is a successful treatment, especially for non-drug-resistant patients with focal epilepsy with structural etiology. The timing of surgery affects the outcomes, and “early” surgery should be preferred to prevent likely drug-resistance and to improve prognosis.